Glucagon and other proglucagon-derived peptides in the pathogenesis of obesity - Holst, Jens Juul (Frontiers in Nutrition, 2022)
Because of differential processing of the hormone precursor, proglucagon, numerous peptide products are released from the pancreatic alpha cells and the intestinal L-cells in which the (pro)glucagon gene is expressed. Of particular interest in relation to obesity are glucagon from the pancreas and oxyntomodulin and GLP-1 from the gut, all of which inhibit food intake, but the other products are also briefly discussed, because knowledge about these is required for selection and evaluation of the methods for measurement of the hormones. The distal intestinal L-cells also secrete the appetite-inhibiting hormone PYY. Characteristics of the secretion of the pancreatic and intestinal products are described, and causes of the hypersecretion of glucagon in obesity and type 2 diabetes are discussed. In contrast, the secretion of the products of the L-cells is generally impaired in obesity, raising questions about their role in the development of obesity. It is concluded that the impairment probably is secondary to obesity, but the lower plasma levels may contribute to the development.